Inhibition of the IGF-1-PI3K-Akt-mTORC2 pathway in lipid rafts increases neuronal vulnerability in a genetic lysosomal glycosphingolipidosis - Tuba Sural-Fehr; Harinder Singh; Ludovico Cantuti-Catelvetri; Hongling Zhu; Michael S. Marshall; Rima Rebiai; Martin J. Jastrzebski; Maria I. Givogri; Mark M. Rasenick; Ernesto R. Bongarzone (The Company of Biologists, 2019)
Glycosphingolipid (GSL) accumulation is implicated in the neuropathology of several lysosomal conditions, such as Krabbe disease, and may also contribute to neuronal and glial dysfunction in adult-onset conditions such as Parkinson's disease, Alzheimer's disease and multiple sclerosis. GSLs accumulate in cellular membranes and disrupt their structure; however, how membrane disruption leads to cellular dysfunction remains unknown. Using authentic cellular and animal models for Krabbe disease, we provide a mechanism explaining the inactivation of lipid raft (LR)-associated IGF-1-PI3K-Akt-mTORC2, a pathway of crucial importance for neuronal function and survival. We show that psychosine, the GSL that accumulates in Krabbe disease, leads to a dose-dependent LR-mediated inhibition of this pathway by uncoupling IGF-1 receptor phosphorylation from downstream Akt activation. This occurs by interfering with the recruitment of PI3K and mTORC2 to LRs. Akt inhibition can be reversed by sustained IGF-1 stimulation, but only during a time window before psychosine accumulation reaches a threshold level. Our study shows a previously unknown connection between LR-dependent regulation of mTORC2 activity at the cell surface and a genetic neurodegenerative disease. Our results show that LR disruption by psychosine desensitizes cells to extracellular growth factors by inhibiting signal transmission from the plasma membrane to intracellular compartments. This mechanism serves also as a mechanistic model to understand how alterations of the membrane architecture by the progressive accumulation of lipids undermines cell function, with potential implications in other genetic sphingolipidoses and adult neurodegenerative conditions. This article has an associated First Person interview with the first author of the paper.